1982
DOI: 10.1590/s0006-87051982000100027
|View full text |Cite
|
Sign up to set email alerts
|

Relação entre matéria orgânica e textura de solos sob cultivo de algodão e cana-de-açúcar, no estado de São Paulo

Abstract: ( l ) Recebido para publicação a 26 de agosto de 1981. No solo, o teor de carbono em equilíbrio com determinado tipo de vegetação é função das adições e da taxa de decomposição da matéria orgânica. Essa relação pode ser expressa pela fórmula: c -bm/k, onde c é a quantidade de carbono orgânico em equilíbrio no solo (t/ha) ; b, a quantidade anual de matéria orgânica (%) adicionada ao solo; m, a taxa de conversão, do material orgânico fresco em carbono orgânico do solo (t/ha), e k, a taxa de decomposição anual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
80

Year Published

1991
1991
2008
2008

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(86 citation statements)
references
References 2 publications
0
6
0
80
Order By: Relevance
“…Em relação às estocagens do LVdf, as capacidades de estocagem de C e N foram de 52,6 e 58,0 % pelo PVAd e 47,2 e 34,2 % pelo RQo. Essa relação direta entre argila e C já foi bem relatada (Lepsch et al, 1982;Lepsch et al, 1994;Feller et al, 1996). Particularmente, as concentrações de C de todos os solos deste trabalho estão de acordo com o gráfico de correlação entre C de solos tropicais e sua textura, elaborado por Feller et al (1996).…”
Section: Matéria Orgânicaunclassified
“…Em relação às estocagens do LVdf, as capacidades de estocagem de C e N foram de 52,6 e 58,0 % pelo PVAd e 47,2 e 34,2 % pelo RQo. Essa relação direta entre argila e C já foi bem relatada (Lepsch et al, 1982;Lepsch et al, 1994;Feller et al, 1996). Particularmente, as concentrações de C de todos os solos deste trabalho estão de acordo com o gráfico de correlação entre C de solos tropicais e sua textura, elaborado por Feller et al (1996).…”
Section: Matéria Orgânicaunclassified
“…Sub-samples of between 500 and 700 mg of finely ground soil were taken from depth intervals to 20 cm, and below this depth subsamples of approximately 1.0 g were utilised. Each sub- 1979Rice a 1986/1987Soybean 1993/1994Soybean and maize 1980/1981Rice 1987/1988Soybean 1994/1995Rice 1981/1982Soybean b 1988Soybean and maize 1995Soybean 1982/1983Pigeon pea c 1989Fallow 1996/1997Maize 1983/1984Fallow 1990/1991Maize 1997/1998Soybean 1984Fallow 1991/1992Soybean 1998/1999Soybean 1985/1986Fallow 1992/1993 Soybean and maize sample was accurately weighed (AE0.1 mg) and placed in a 250 ml digestion tube to which was added 10 ml of an aqueous solution of potassium dichromate (50 g L À1 ) and the tube agitated until all of the soil was moist. To this tube was slowly added 20 ml of concentrated sulphuric acid with gentle agitation.…”
Section: Soil Sampling and Analysesmentioning
confidence: 99%
“…Many studies in tropical and subtropical regions have shown that there is a positive relationship between silt + clay concentration of low activity clay (LAC) soils and their C concentration (Jones, 1973;Turenne, 1977;Talineau et al, 1980;Lepsch et al, 1982Lepsch et al, , 1994Feller et al, 1991). In a study on 65 different LAC soils from West and Central Africa, West Indies, Brazil and Southern India, Feller et al (1991) reported that there was strong positive linear relationship between clay + silt (cs) concentration and concentration of total organic carbon (TOC) in top 20 cm of these soils (C = 0.037(cs) + 0.69, r = 0.87 *** ).…”
Section: Total Soil C and N Concentrationsmentioning
confidence: 99%
“…Feller and Beare (1997) established limits of SOC based on the silt + clay content of tropical kaolinitic soils from several tropical countries, providing several regression equations to calculate the original SOC level and depleted levels. Lepsch et al (1981Lepsch et al ( , 1994 found the SOM content in the top 20 cm of soils that had been cropped for many years in oxisols and ultisols of Brazil without the d modifier could be calculated by the equation %SOM = 0.773 + 0.0325 (silt + clay, %), r = 0.81***.…”
Section: Soil Organic Carbon Saturation Deficitmentioning
confidence: 99%